An atractive merhod to reach circular polarization - Paz Barrera, Steven Jesús; Seguí Camacho, Frank; Marante Rizo, Francisco (Telemática, 2022)
This article proposes the design and simulation of a microstrip antenna with circular polarization in the 2.4 GHz band. Circular polarization is achieved using an attractive method, positioning the microstrip feeder on the lateral axis of a hexagonal patch, and making contact with it. This reaches a good match to the 50-ohm line and a shape of the radiation pattern that can be useful. The use of low-cost materials and the simple structure of this antenna make it suitable for being subjected to different techniques to increase bandwidth. The entire design, simulation, and optimization process was carried out in the CST Studio Suite 2021 software and with the help of PCAAD.